UJI ADAPTASI LINGKUNGAN DENGAN BERBAGAI MACAM MULSA ORGANIK PADA TANAMAN TEMBAKAU (Nicotiana tabacum L.) VARIETAS BESUKI NA OOGST - Widiyani, Dimas Prakoswo; Sanjaya, Refki; Nataris, Galuh Bintang; Anissa, Nabillah; Soleha, Soleha; Ningsih, Eka Wahyu (Universitas Lampung, 2025)
Tobacco (Nicotiana tabacum L.) is an important commodity in the Indonesian economy, but plant growth and production are often hampered by environmental factors such as climate change and suboptimal soil conditions. Organic mulch can be a solution to improve soil quality and support plant growth in adapting climate change. This study aimed to test the effect of various types of organic mulch on the growth and production of Besuki Na-Oogst tobacco plants in Lampung Province. The study was conducted at the Lampung State Polytechnic from September to December 2024 using a Randomized Block Design (RBD) with various types of organic mulch treatments (sengon litter, cogongrass, and oil palm empty bunches) and analyzed using analysis of variance at the 5% level and continued with the Duncan multiple ring test (DMRT) 5%. The results showed that Palm oil empty fruit bunch mulch gave the best results, with an average dry stalk reaching 248.4 grams per stem, an average plant height reaching 101.8 cm, and an average number of leaves of 15.0 leaves at 3-month plant age observation, better than the control. However, the use of organic mulch did not show a significant difference in stem diameter, the impact was more visible in other components such as the number of leaves and dry stalk.